ANTIPROLIFERATIVE ACTIVITY OF BERBERINE IN VITRO AND IN VIVO - Letasiova, Silvia; Jantova, Sona; Muckova, Marta; Theiszova, Marica (Biomedical papers, 2005)
Berberine, an isoquinoline plant alkaloid acted cytotoxically in vitro on tumour cell lines B16. Its anticancer activity in vivo was studied with the transplanted B16 line in the range of doses from 1 mg/kg to 10 mg/kg. The significant reduction of tumor volume was observed on day 16 at doses of 5 and 10 mg/kg. The dose of 1 mg/kg stimulated the tumor mass, but other tested concentration, 5 and 10 mg/kg, reduced the tumor weight.
Keywords: Berberine/B16 cells/C57BL/6 mice/Antiproliferative activity